Influence of nutrient sources and weed control measures on weeds and yield of baby corn - Dhar, Niranjan Kumar; Dhar, Shiva; Kumar, Ashok (Annals of Agricultural Research, 2016)
A field experiment was conducted during kharif season of 2008 at the Experimental Farm of Divisionof Agronomy, Indian Agricultural Research Institute, New Delhi. The experiment was laid out in afactorial randomized block design and replicated thrice with the combination of 4 nutrient sources:120-26.4-41.7 kg N-P-K/ha through fertilizers, 120 kg N through FYM, leaf compost and throughvermicompost and 4 weed management practices: unweeded control, weed free check, two handweeding at 20 and 40 days after sowing and application of atrazine @ 0.5 kg + pendimethalin @ 0.75kg/ha tank mixed as pre-emergence (PE). The experiment was conducted on baby corn 'PEHM2'tostudy the effect of nutrient sources and weed control measures on weed control, nutrients removalby weeds, change in soil fertility and the economic returns. Result revealed that number of weedsand weed dry matter were unaffected by different sources of nutrients except in case of FYMapplication either with two hand weeding at 20 & 40 DAS or application of atrazine @ 0.5 kg +pendimethalin @ 0.75 kg/ha as PE. The number of monocot and dicot weeds and weed dry matterat both the stages were significantly higher in the unweeded control in comparison with remainingtreatments, however, two hand weeding at 20 DAS and 40 DAS and application of atrazine @ 0.5 kgand pendimethalin @ 0.75 kg/ha as PE were remained at par.